A Study on Moral Values Represented in Shawshank Redemption Movie - Marlina, Titik Heni; Kustantinah, Indri; Widiyanto, Muhammad Wahyu (Universitas PGRI Semarang, 2021)
This research analyzed Shawshank Redemption movie, a movie by Frank Darabont. This movie told about the struggling of Andy Dufresne who was accused of the murder of his wife and her affair. This research focused on moral value of the movie. The methodology of this research is descriptive qualitative method. This study aims to found the moral values of Shawshank Redemption movie. Documentation method was used to collect the data and descriptive analysis technique to analyze the data. The results of this study are the moral values found in the Shawshank Redemption movie; honestly, hard work, unconditional love and kindness, compassion, and co-operation. Then hard work as the most dominant moral value appears in the Shawshank Redemption movie, because this moral value often occurs in this movie.Â